Meds to Beds at Hospital Discharge Improves Medication Adherence and Readmission Rates in Select Populations. Issue 3 (March 2023) - Stedge, Bonnie; Xu, Jennifer; Kubes, Julianne N.; Han, Erica; Russie, Christa; Woods, Lou; O'Donnell, Christopher
Abstract : Medication nonadherence caused by difficulty obtaining and paying for medicines can increase hospital readmissions. This project implemented a predischarge medication delivery program at a large urban academic hospital and provided subsidized medications for uninsured and underinsured patients to reduce readmissions. The authors describe the outcomes of this intervention in terms of readmissions and analyze the impact on individuals with different numbers of comorbidities. Abstract: Objectives: Medication nonadherence caused by difficulty obtaining and paying for medicines can increase hospital readmissions. This project implemented Medications to Beds ("Meds to Beds, " M2B), a multidisciplinary predischarge medication delivery program, at a large urban academic hospital that provided subsidized medications for uninsured and underinsured patients to reduce readmissions. Methods: This 1-year retrospective analysis of patients discharged from the hospitalist service after implementing M2B contained two groups: one with subsidized medications (M2B-S) and one with unsubsidized medications (M2B-U). Primary analysis was 30-day readmission rates for patients, stratified by Charlson Comorbidity indexes (CCIs) of 0, 1–3, ≥4 to represent low, medium, and high comorbidity burden. Secondary analysis included readmission rates by Medicare Hospital Readmission Reduction Program diagnoses. Results: Compared with controls, the M2B-S and M2B-U programs had significantly reduced readmission rates among patients with CCIs of 0 (10.5% [controls] vs 9.4% [M2B-U] and 5.1% [M2B-S], P < 0.05). A nonsignificant reduction occurred in readmissions for patients with CCIs ≥4 (20.4% [controls] vs 19.4% [M2B-U] vs 14.7% [M2B-S], P < 0.07). Patients with CCIs of 1 to 3 showed a significant increase in readmission rates in the M2B-U, but a decrease in readmission rates among the M2B-S (15.4% [controls] vs 20% [M2B-U] vs 13.1% [M2B-S], P < 0.05). Secondary analyses found no significant differences in readmission rates when patients were stratified by Medicare Hospital Readmission Reduction Program diagnosis. Cost analyses demonstrated that subsidizing medicines cost less per patient for every 1% readmission reduction than delivery alone. Conclusions: Providing medicine to patients predischarge tends to lower readmission rates for populations with no comorbidities or with a high burden of disease. This effect is amplified when prescription costs are subsidized.